Corporate governance: inside - S. I. Lutsenko (Real Economics Publishing House, 2018)
Features of corporate governance are considered. In modern realities quality of corporate governance is determined by the internal organization (accurate corporate strategy with determination of the purposes and interests of the company). The author offers corporate model which would consider interests not only shareholders, but also other interested participants.